Teacher And Students’ Perception Towards The Use Of Speaking Board Games In Online English-Speaking Lesson In Senior High School - Yani, Muhammad; Nurfidah, Nurfidah; Khairunnisah, Noni Antika (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Speaking board games is one of the strategies used in English learning process in order to improve students' speaking skills, however, during the coronavirus disease (COVID 19), these speaking board games were applied using online classroom. In learning process, the used speaking board games in online classroom, the teacher can apply speaking board games strategies to improve students' speaking skills. This research aims to know the teacher and students’ perception in English learning the use speaking board games in online classroom. This research used a qualitative descriptive, the conducted in-dept interview with the teacher and four students. The results of this research show a positive response when using speaking board games strategy in online classroom. In applying the speaking board games strategy in online classroom, the teacher and 4 students get the benefits. The teacher has the advantage of increasing student creativity. Furthermore, the students also get the benefit of helping to improve their speaking skills, get to learn via the internet, and get a new knowledge. However, the teacher and students also experience some difficulties when used speaking board games strategy in online classroom. The concern experienced by the teacher is internet connection, and it is difficult to control students, students' understanding. In addition, students' difficulties include internet connection, knowledge of technology, and student preparation.